2023
DOI: 10.3390/foods12091900
|View full text |Cite
|
Sign up to set email alerts
|

Research on Online Nondestructive Detection Technology of Duck Egg Origin Based on Visible/Near-Infrared Spectroscopy

Abstract: As living standards rise, people have higher requirements for the quality of duck eggs. The quality of duck eggs is related to their origin. Thus, the origin traceability and identification of duck eggs are crucial for protecting the rights and interests of consumers and preserving food safety. As the world’s largest producer and consumer of duck eggs, China’s duck egg market suffers from a severe lack of duck egg traceability and rapid origin identification technology. As a result, a large number of duck eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Therefore, the data at both ends were excluded and the effective wavelength range in the middle was retained for further analysis, using 463 nm and 980 nm as the boundaries. Although the penetration and waveform of the spectral curves can be affected by species ( Dong et al, 2019b ; Li et al, 2023c ), the overall waveforms of the curves were found to be similar to the penetration spectral patterns observed in previous studies ( Zhang et al, 2015 ; Dong et al, 2019a ). Two distinct peaks and one valley were observed in the spectral curves.…”
Section: Resultssupporting
confidence: 79%
“…Therefore, the data at both ends were excluded and the effective wavelength range in the middle was retained for further analysis, using 463 nm and 980 nm as the boundaries. Although the penetration and waveform of the spectral curves can be affected by species ( Dong et al, 2019b ; Li et al, 2023c ), the overall waveforms of the curves were found to be similar to the penetration spectral patterns observed in previous studies ( Zhang et al, 2015 ; Dong et al, 2019a ). Two distinct peaks and one valley were observed in the spectral curves.…”
Section: Resultssupporting
confidence: 79%
“…This study involved a substantial dataset of 480 samples. Similarly, Li et al. (2023) harnessed the power of CNNs coupled with spectroscopy to identify the provenance of duck eggs, utilizing a dataset encompassing 261 samples.…”
Section: Methodsmentioning
confidence: 99%
“…This study involved a substantial dataset of 480 samples. Similarly, Li et al (2023) harnessed the power of CNNs coupled with spectroscopy to identify the provenance of duck eggs, utilizing a dataset encompassing 261 samples. Furthermore, Hu et al ( 2023) applied a one-dimensional convolutional neural network in conjunction with spectroscopy to detect pesticide residues on the Hami melon surface.…”
Section: Cotton-netmentioning
confidence: 99%
“… Lin et al (2022) pointed out that compared with traditionally traceable beef, consumers are willing to pay higher prices for beef that is traceable through blockchain technology. In addition, Rodriguez-Salvador and Dopico (2020) , Jin et al (2023) , and Li et al, (2023) considered that due to rising consumer income levels and improved knowledge about food safety science, demand for FEBT will be increased, which will stimulate enterprises to employ the BTS.…”
Section: Literature Reviewmentioning
confidence: 99%